Unilateral triple renal artery as an anatomical variant - case study - Wróbel, Grzegorz (Journal of Education, Health and Sport, 2018)
Knowledge of the renal vascular system is extremely important in everyday clinical practice. In kidney transplantation, knowledge about the amount, diameter of a blood vessel, and the course of arteries and renal veins are critical in the selection of kidneys to be taken and planning operations. Multi-detector CT provides quick, accurate determination of the anatomical location and course of the renal vessels. Additional renal arteries have been reported in different population groups. The study concerned a 65-year-old male subjected to imaging diagnostics using computed tomography for oncological purposes. During the analysis of the image, the presence of three renal arteries emerged directly from the abdominal aorta and proceeded in the direction of the renal hilum.